Pelaksanaan Sema 4 Tahun 2010 Bagi Pelaku Penyalahgunaan Narkotika Dalam Penyidikan Kepolisian - Arief Wibowo; I Made Minggu Widyantara; Ni Made Sukaryati Karma (Fakultas Hukum Universitas Warmadewa, 2019)
Abstract The process of investigating narcotics crimes does not only refer to the Criminal Procedure Code but also refers to Sema Number 4 of 2010 concerning the management of investigations conducted by the police, the problem is How to regulate the police investigation process against perpetrators of narcotics abuse? And how do you place the perpetrators of abuse in Sema number 4 in 2010? The method used by normatif is conducting field research through interviews sourced from primary data and secondary data, then processed descriptively qualitatively. The arrangement of the police investigation process against perpetrators of narcotics abuse is regulated in the Criminal Procedure Code where police investigators are given investigations to case files. The implementation of the investigation originated with the existence of a report, There is a complaint, in the case of being caught and investigators have begun to investigate an event which is a criminal act the investigator notifies the prosecutor.